2021
DOI: 10.24198/sosiohumaniora.v23i2.30296
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Inspectorate in Supervision of Government Administration in Buru Selatan Regency

Abstract: This article investigated Performance of the Inspectorate in Supervision of Government Administration in Buru Selatan Regency. The type of study used was descriptive research. This would provide a factual depiction regarding the application of Inspectorate function of Buru Selatan Regency. This study aimed to analyze the performance of the Inspectorate in Supervision of Government Administration in Buru Selatan Regency. This study suggested that the application of supervision either perceived from the inspecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 3 publications
0
4
0
6
Order By: Relevance
“…Keberhasilan kompetensi kebutuhan individu sangat mempengaruhi kebutuhan organisasi (McKenna, 2010). Temuan Selano, Wance (2021) performance sangat menentukan peningkataan kinerja, perubahan paradigma pelayanan (Herizal, Mukhrijal, Wance, 2020), pemanfaatan teknologi informasi (Ekram, Tuanaya, Wance, 2022), evaluasi pelayanan (Wance, 2019), kinerja pegawai (Suhu, Ibrahim, dkk, 2023).…”
Section: Pendahuluanunclassified
“…Keberhasilan kompetensi kebutuhan individu sangat mempengaruhi kebutuhan organisasi (McKenna, 2010). Temuan Selano, Wance (2021) performance sangat menentukan peningkataan kinerja, perubahan paradigma pelayanan (Herizal, Mukhrijal, Wance, 2020), pemanfaatan teknologi informasi (Ekram, Tuanaya, Wance, 2022), evaluasi pelayanan (Wance, 2019), kinerja pegawai (Suhu, Ibrahim, dkk, 2023).…”
Section: Pendahuluanunclassified
“…Pegawai pada Bagian Protokol dan Komunikasi Pimpinan diwajibkan untuk memiliki kompetensi saat bekerja agar dapat menampilkan diri dan memberikan hasil kerja yang optimal sesuai tugas pokok dan fungsi yang ada. Perubahan paradigma dalam melakukan pelayanan (Herizal, Mukhrijal, Wance, 2020), efektivitas pelayanan (Selanno, Wance, 2021), teknologi infomasi untuk melakukan layanan public (Ekram, Tuanaya, Wance, 2022), kualitas pelayanan (Wance, 2022), evaluasi pelayanan oleh pemerintah (Wance, 2019).…”
Section: Kesesuaian Beban Tugas Dengan Kompetensiunclassified
“…The idea of NPM illustrates a shift in the concept of government to governance which requires synergy between the government, the private sector, and the community in the delivery of good and quality public services. The presence of the New Public Service (NPS) initiated by Denhart and Denhardt (2003), whose basis is not much different from the demand for participatory governance or democratic governance, continues to strengthen and has become a paradigm of public administration in today's global society (Dwiyanto, 2015).The result suggested that the knowledge in the field of work was still low (Selanno, H., & Wance, 2021).…”
Section: Good Public Servicementioning
confidence: 99%